Difusión del software educativo como apoyo didáctico en el área de estudios sociales del nivel de educación general básica enmarcado a los hechos históricos, geográficos y educativos del cantón Espíndola de la provincia de Loja - Troya Ordoñez, Andrea Elizabeth (2015)
The overall objective of this research is to disseminate educational software and teaching support in the area of Social Studies General Basic Education level, framed to the Historical, Geographical and Educational made Espindola canton in the province of Loja, educational software contains relevant information that was used for the benefit of the teacher and student, as a teaching resource for the teaching-learning process. Where the thesis research was performed in Region 7, Province of Loja, Canton Espindola, taking into account urban and three rural parish there seven educational units were selected, which had the technological and educational equipment necessary for the use of educational software. To test the effectiveness of this thesis were taken as observation instruments, survey and tests applied before and after the use of educational software in mind, the same that allowed the achievement of the objectives originally proposed in the draft research. The work concluded with effective results showing that the educational software was beneficial to students, rescuing their identity, promote and expand knowledge and values in them and leaving the scope of a new instructional support teacher for the area of Social Studies.